Evolution of a soft‐tissue foraging adaptation in African cichlids: Roles for novelty, convergence, and constraint. (2nd September 2019) - Conith, Moira R.; Conith, Andrew J.; Albertson, R. Craig
Abstract: Understanding the origins of biodiversity demands consideration of both extrinsic (e.g., ecological opportunity) and intrinsic (e.g., developmental constraint) factors. Here, we use a combination of phylogenetic and genetic tools to address the origin of novelty in African cichlids. In particular, we focus on an extreme hypertrophied snout that is structurally integrated with the upper jaw. We show that this bizarre trait has evolved independently in at least two distinct and ecologically successful cichlid clades. We find that snout dimensions are decoupled both phenotypically and genetically, which has enabled it to evolve independently in multiple directions. Further, patterns of variation among species and within a genetic mapping pedigree suggest that relative to snout length, depth is under greater genetic and/or developmental constraint. Models of evolution suggest that snout shape is under selection for feeding behavior, with snout depth being important for algae scraping and snout length for sand sifting. Indeed, the deep snout of some algivores is achieved via an expansion of the intermaxillary ligament, which is important for jaw stability and may increase feeding performance. Overall, our data imply that the evolution of exaggerated snout depth required overcoming a genetic/developmental constraint, which led to expanded ecological opportunity via foraging adaptation.